2006
DOI: 10.1016/j.amjhyper.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-h Shift Work in the Emergency Room on Ambulatory Blood Pressure Monitoring Values of Medical Residents

Abstract: Working in the ER on a 24-h shift leads to abnormal BP behavior in medical residents, thus suggesting that this type of work may be a risk factor for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
0
21
0
3
Order By: Relevance
“…It is now well-accepted that inflammation has an important role in the development of cardiovascular disease and that each of the inflammatory markers we measured predicts cardiovascular disease (14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Epidemiologic studies convincingly show an increased prevalence of cardiovascular disease in night workers versus day workers, and field studies in shift workers have shown increased blood pressure and inflammatory markers during or after night work compared with day work or days off (41)(42)(43)(44)(45). However, such studies can not definitively distinguish a possible causal role of circadian misalignment in the observed adverse health effects of shift work versus that of differences in other factors, such as work stressors, dietary habits, and physical activity, as well as family, financial, genetic, health, and social factors, etc.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is now well-accepted that inflammation has an important role in the development of cardiovascular disease and that each of the inflammatory markers we measured predicts cardiovascular disease (14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Epidemiologic studies convincingly show an increased prevalence of cardiovascular disease in night workers versus day workers, and field studies in shift workers have shown increased blood pressure and inflammatory markers during or after night work compared with day work or days off (41)(42)(43)(44)(45). However, such studies can not definitively distinguish a possible causal role of circadian misalignment in the observed adverse health effects of shift work versus that of differences in other factors, such as work stressors, dietary habits, and physical activity, as well as family, financial, genetic, health, and social factors, etc.…”
Section: Discussionmentioning
confidence: 86%
“…In chronic shift workers, blood pressure is higher, and the day/night blood pressure rhythm is blunted while working night shifts compared with day shifts (41)(42)(43)(44)(45). Such study designs can not isolate the independent effect of circadian misalignment on blood pressure versus shift workinduced changes in factors such as diet, physical activity, light exposure, etc.…”
Section: Possible Mechanisms Involved In Circadian Misalignment-mediatedmentioning
confidence: 99%
“…In a study by Yamasaki et al (118), shift workers had a smaller drop in the systolic blood pressure during sleep than day workers, and they were more often categorized as "non-dippers". Shift work has also been associated with higher 24-hour blood pressure levels (119,120), while the risk of non-dipper status yielded mixed results. The mean systolic blood pressure during a 24-hour measurement has been found to be higher among shift than day workers (110).…”
Section: Metabolic Syndrome (Mets)mentioning
confidence: 95%
“…The cohort consists of 18,558 individuals: born in one week in March 1958 in England, Scotland and Wales (17,638) with the addition of immigrants (n = 920) with the same birth dates up to age 16 years [23]. At 45 years, 11,971 cohort members who had not died or emigrated, were still in contact with the survey, and who were able to provide informed consent were invited to a clinical examination undertaken in their home by a trained nurse; 9,377 (78%) participated.…”
Section: Study Sample and Designmentioning
confidence: 99%
“…Night-work is estimated to increase the risk of coronary heart disease (CHD) by 40% [7]. Adverse changes have also been reported for a range of CVD risk factors although findings are inconsistent due to methodological differences [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%